TAFSIR DAN SAINS: STUDI ATAS KOMPATIBILITAS DAN KONTRADIKSI ANTARATAFSIR AL-QUR'AN DAN ILMU SAINS MODERN - Sodikin, Sodikin; Sani, Azwar (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research investigates the relationship between the interpretation of the Qur'an and modern science in the era of globalization, evaluating their compatibility and potential contradictions. Utilizing content analysis and literature review, this research aims to uncover how both fields view natural phenomena, identifying similarities and differences in their interpretations. More than just highlighting existing differences, such as in the debate on the theory of evolution, this research seeks to find potential synergy between the spiritual views in the Qur'an and modern scientific findings. The results of the study are expected to provide deeper insights into each discipline's perspectives on the universe and to promote dialogue between the two fields often considered as conflicting. The ultimate aim is to enrich critical thinking and contributions to science, as well as provide a reference for further research on the interaction between the interpretation of the Qur'an and science. It aims to facilitate a more integrative and holistic understanding, encouraging collaboration between religion and science for a broader understanding of the world.